High-speed fiber laser cutting of thick stainless steel for dismantling tasks. (1st September 2017) - Shin, Jae Sung; Oh, Seong Yong; Park, Hyunmin; Chung, Chin-Man; Seon, Sangwoo; Kim, Taek-Soo; Lee, Lim; Choi, Byung-Seon; Moon, Jei-Kwon
Highlights: A new cutting head and our own laser cutting techniques were developed for dismantling tasks. The cutting performance was studied using the developed cutting head and a 6-kW laser power. For the 60-mm thick stainless steel plate cutting, a maximum cutting speed of 72 mm/min was obtained. To the best of our knowledge, this speed is the highest when cutting with 6-kW laser power. Abstract: A high-speed fiber laser cutting technology of thick steels for dismantling tasks was achieved using a 6-kW fiber laser system. At first, a new cutting head for efficient cutting of thick steels was developed, which was composed by a collimator with a focal length of 160 mm and mirror-type focusing objects with a long focal length of 600 mm. The long focal length of the focusing object made it possible for the beam size to be small through the thick cutting material and the cutting efficiency was expected to increase compared with the short focal length. In addition, folding the beam facilitated the compact cutting head with a size of 160 mm (width) × 80 mm (height) × 640 mm (length) and a weight of 6.9 kg. In the cutting experiment, the laser beam was delivered to the cutting head by a 25-m long process fiber with a core diameter of 100 μm. The cutting performances were studied against the thicknesses of stainless steel plates. A maximum cutting speed of 72 mm/min was obtained for the 60-mm thick stainless steel plate cutting and the cut specimen showed an excellent kerf shape and a narrow kerf width. To the best of our knowledge, this cutting speed was higher than other previously reported results when cutting with a 6-kW laser power.